Relevance of Qualitative Research Approach in Evaluating Mental Health Interventions among Victims of Violence - Pacichana-Quinayaz, Sara G.; Osorio-Cuellar, Gisel V.; Gonzalez, Stephanie; Bonilla-Escobar, Francisco Javier; Gutierrez-Martinez, Maria I. (International Journal of Medical Students, 2015)
NA